Full solar spectrum photocatalytic oxygen evolution by carbon-coated TiO2 hierarchical nanotubes - Liang, Zhangqian; Bai, Xiaojuan; Hao, Pin; Guo, Yichen; Xue, Yanjun; Tian, Jian; Cui, Hongzhi (Applied catalysis. B, Environmental, 2019)
[Display omitted] •Hierarchical TiO2 nanotube with uniform carbon coatings is synthesized successfully.•The TiO2/C hierarchical nanotube exhibits the best photocatalytic activity under full solar spectrum light irradiation.•The incorporation of visible/NIR light active carbon coating with UV light responsive TiO2 promote solar utilization.•The hierarchical nanotube can generate multiple reflections of incident light to promote an efficient light harvesting.•The generated carbon coatings on the surface of TiO2 facilitate electron-hole separation. Smart architectures of TiO2 are attracting increasing attention due to their outstanding properties in a broad range of fields. Herein, hierarchical TiO2 nanotube with uniform carbon coatings is synthesized as the full solar spectrum photocatalytic materials for O2 evolution by a facile solvothermal method. This unique structure consists of an interstitial hollow spaces and a functional nanotube shell assembled from two-dimensional (2D) nanosheets. By adjusting the types of solvents and reaction time, the morphologies of TiO2/C composites can be tuned to nanoparticles, nanorods, or hierarchical nanotubes. Among these morphologies, the TiO2/C hierarchical nanotube exhibits the best photocatalytic activity and favorable stability toward oxygen evolution from water oxidation under full solar spectrum light irradiation. The reason is attributed to the desirable incorporation of visible/near-infrared (NIR) light active carbon coating with UV light responsive TiO2 for promoted solar energy utilization. Besides, the solvothermal step leads to hierarchical nanotube structures which can generate multiple reflections of incident light so as to promote an efficient light harvesting due to an enhanced specific surface area (244.4 m2 g−1) and light scattering ability. Moreover, the generated carbon coatings on the surface of TiO2 facilitate electron-hole separation.